Enhancing dietary adherence among African-American adolescents: the role of parenting styles and food-related practices - Ardakani, Azam; Monroe-Lord, Lillie; Wakefield, Dorothy; Castor, Chimene (Frontiers in Nutrition, 2024)
Introduction Parenting styles (PSs) and food-related parenting practices (FPPs) play a crucial role in shaping adolescent eating behavior. This study aimed to investigate the relationship between the different PSs and FPPs of African-American families and the frequency of consumption of MyPlate food items by adolescents based on recommendations from the Dietary Guidelines for Americans (DGA). Methods This study used a cross-sectional design. Data collection was conducted using Qualtrics through an online survey of 211 African-American parents and their adolescents aged 10–17-year-old. Adolescents completed the Youth and Adolescent Food Frequency Questionnaire to assess their dietary behavior, while parents filled out the survey to identify the degree of PSs (i.e., authoritative, authoritarian, setting rules, and neglecting) and FPPs (i.e., monitoring, reasoning, copying, and modeling). Spearman’s rank correlation coefficient, Wilcoxon rank-sum test, and stepwise logistic regression were performed to determine the answers to the research questions. Results For fruit consumption, authoritative parenting significantly reduced the likelihood of adherence to DGA, while authoritarian, monitoring, and reasoning practices increased it. Female adolescents were more likely to meet fruit intake recommendations, with a similar positive impact observed for those whose parents had above high school education. In vegetable intake, authoritarian and monitoring practices positively impact on adherence to DGA, whereas setting rules had a detrimental impact. Being in a married household also increased vegetable intake DGA adherence. For grain consumption, reasoning was a significant positive predictor, while setting rules negatively impacted adherence. Dairy DGA adherence was positively impacted by monitoring and copying practices, but negatively impacted by female gender. Protein intake showed a positive association with reasoning and parental education. Discussion Our findings confirm the importance of parenting in developing desired eating behaviors among African-American adolescents. The results of this study can be used to develop culture-based nutritional education programs for parents and youth.